O жизни, науке, судьбе - Kozłyk, Ihor (Acta Polono-Ruthenica, 2019)
The review deals with the comparative analysis of the second edition of the book by Kharkiv literary critic, Doctor of Philology, Professor Leonid Genrikhovich Frizman (1935–2018) “In the circles of literary critics: Memoirs essays”, published in Kyiv and Moscow in 2017. The history of the book is described in the context of the author’s creative practices and similar experiences of Russian and Ukrainian literary critics; its substantive focus, the concept embodied in it, the personal composition, style, architectonics, illustrative component and artistic design are characterized in the review. The focus is on the study of the semantic role of the corrections and additions, made by the author in the second edition. The analysis takes into account the existing critical experience of perception of the first edition of memoirs in Russia to avoid unnecessary repetition.